Climate-biodiversity nexus in transnational climate governance: variation across net zero initiatives - Yixian Sun; Natalie Page (Carbon Management)
The Glasgow Climate Pact recognizes the importance of biodiversity protection for climate action. While climate and biodiversity governance processes remain separated at the intergovernmental level, transnational initiatives may provide opportunities to better integrate these two important issues. If linkages between the two cannot be well managed in transnational action, we might be running the risk of achieving a net zero economy at the expenses of nature. How do transnational governance initiatives understand and address the linkages between climate change and biodiversity protection? We tackle this question by assessing the targets on biodiversity identified by 25 partner initiatives of the Race to Zero – a UN-backed campaign with clear criteria to rally non-state and subnational action for achieving net zero by 2050. Our study shows variation within the campaign: 28% of its partner initiatives did not consider biodiversity at all, whilst 36% of the partner initiatives have identified detailed commitments and action plans to ensure no harm on biodiversity. Overall, more than two-thirds of the partner initiatives had mentioned the role of biodiversity in climate action. Considering possible explanatory factors of the variation observed, we suggest that the target sector and engagement with environment-oriented organizations are likely to lead transnational governance initiatives to consider biodiversity alongside emission reductions in net zero strategies and commitments. The study sheds light linkages between climate mitigation and biodiversity protection in the recent net zero movement and proposes policy recommendations for transnational initiatives to better integrate climate and biodiversity targets.